Kajian Pemetaan Komoditas Kelapa Sawit (Elaeis guineensis jacq.) Pada Skripsi, Tesis dan Disertasi IPB sampai tahun 2022 - Ratnaningsih; Himawan Deden; Lindawati (Jurnal Pustakawan Indonesia, 2022)
Introduction. This study aims to determine the number and distribution of thesis research, theses and dissertations of IPB students related to oil palm commodities from various aspects that include it. The mapping of this field of science is expected in the future to become important and useful information related to the development of oil palm research at IPB University. Research Method This research uses descriptive quantitative method. The population is all thesis, thesis and dissertation data for IPB students related to palm oil commodities until 2022, obtained from the IPB Repository. The data was tabulated using Microsoft Excel and the data processing of science and keyword maps was using VOSviewer.Research result. There are 2,346 researches on oil palm commodities, most of which are found in the Faculty of Agriculture with 39% and the distribution in the Agricultural Industrial Technology Study Program is 11% for theses and 30% for dissertations. Mapping the distribution of oil palm research keywords found popular keywords that are widely used related to "processing" with the occurrence rate of each thesis collection 768 times; thesis 229 times; dissertation 63 times. The productivity of research supervisors related to oil palm found in the thesis is Sudirman Yahya with 66 studies; thesis is Sudrajat with 20 studies; Sudirman Yahya dissertation as many as 6 studies.Conclusion. Research on oil palm commodities is dominated by the field of "processing" science, most research is carried out at the Faculty of Agriculture, and the Agricultural Industrial Technology Study Program. The supervisors who are productive in encouraging research related to oil palm are Sudirman Yahya and Sudrajat.